PERKEMBANGAN PENDIDIKAN ISLAM DI RA AL FATAH TEGALSARI GARUNG WONOSOBO MELALUI BUMDES TIRTA ANUGERAH - Miftahudin, Miftahudin (AL-QALAM: JURNAL KEPENDIDIKAN, 2023)
Village-Owned Enterprises (BUMDes) are business entities whose capital is wholly or largely owned by the Village through direct participation originating from separated Village assets to manage assets, services and other businesses for the welfare of the village community. Bumdes Tirta Grace is managed by the village in the form of a warm water bath business unit and a morning market which has generated original village income, part of which is given to underprivileged students amounting to 25 percent for scholarship assistance for students. In determining the 2023 RKPdes, the village refers to the motto and goal, namely sustainable human resource development, meaning sustainable cadres for the village generation. The target for students who can take part in receiving an education equal to the wider community is to understand Islamic education. Of course, to understand it, it is not understood as an established and systematic educational system, but rather the educational process occurs more incidentally and perhaps even more in the form of answers to various problems that developed at that time. Education in Islam, linguistically, has a different meaning. very varied. This difference cannot be separated from the many terms that appear in the Al-Qur'an and Al-Hadith as the main reference source for Islamic education which mention words (kalimah) which have educational or teaching connotations.